Monetary Policy Crisis Management as a Threat to Economic Order - Andreas Freytag; Gunther Schnabl (Center for Economic Studies and ifo Institute (CESifo), 2017)
The paper analyses the effects of the monetary policy crisis management of the European Central Bank on the economic order of Germany. It is argued that in post-war Europe the German social market economy as designed by Eucken (1952) and Müller-Armack (1966) has been a core element of growth, welfare, social cohesion and political stability in Germany and Europe as a whole. It is shown that the monetary policy rescue measures of the European Central Bank have undermined the constitutive principles of the German social market economy, what has considerably contributed to the erosion of (productivity) growth and welfare in Germany and Europe. As the outcome is crumbling social cohesion and growing political instability, a timely exit from ultra-expansionary monetary policy is postulated.
Keywords: B20; E14; B25; 330; economic order; social market economy; Soziale Marktwirtschaft; Germany; Walter Eucken; Alfred Müller-Armack; monetary policy; crisis management